(Re)producing an ‘Islamic-Byzantine’ Artist - Adila Laïdi-Hanieh (Manazir Journal)
This article challenges the interpretation of Fahrelnissa Zeid’s (1901–1991) mid-century abstract production as influenced by Islamic and Byzantine art. The study analyzes culturalist presentations of the artist’s exhibitions in Paris galleries (1949–1969) and later international exhibitions (1990–2024), comparing them with the artist’s own statements and alternative reviews. I argue that both twentieth century and contemporary interpretations of her abstract practice are orientalist in character. The original elision of her voice reflected mid-century colonial ideology and promoted a new Parisian lyrical abstraction movement, while contemporary interpretations elevate globalized exhibitions’ marketing over scholarship. These culturalist interpretations exclude Fahrelnissa Zeid from modernism’s narratives by framing her practice as a-historic cultural atavism. I argue that Fahrelnissa’s approach to abstraction was shaped by her preoccupation with all-encompassing other-worlds. Her transition to abstraction followed a figurative expressionist phase and was triggered by paradigm-shifting visual shocks, leading to a two-decade gestural expressionist production. Fahrelnissa Zeid’s artistic vision also differs from some Global South modernist artists’ practice who sought to hybridize their national cultural imageries with European visual styles.